PEMBERDAYAAN IBU RUMAH TANGGA UNTUK MENJADI SEORANG WIRAUSAHA, DI WILAYAH RW 09, KAMPUNG BULAK, KELURAHAN BENDA BARU, KECAMATAN PAMULANG, TANGERANG SELATAN – BANTEN - Adji Widodo; Anah Furyanah; Sugeng Widodo; Haidilia Maharani; Dien Mardiana Yulianti; Ibnu Sina (LPPM Universitas Pamulang, 2020)
The aim of community service is to equip housewives in RW 09, Kampung Bulak, Pamulang, to be able to carry out entrepreneurial activities so as to provide additional income for the family. Participants in this service were mothers who included PKK cadres, Posyandu, Jumantik and orchid growers in the Women Farmers Group (KWT). The service method used is a survey method and direct counseling related to entrepreneurship, selection of business forms, and financial management of small businesses that are good and effective. The last was a visit to one of the residents' orchid gardens. The conclusion of this dedication is that Bulak Village is already crowded with large housing like Vila Dago and Griya Asri Pamulang, so business opportunities can be run to support the needs of the local population, such as groceries, food stalls, rented houses and others. And for women orchid farmer group members can apply tips in business management including managing finances well and effectively in the future.Keywords: Entrepreneurship, Housewives, Women Farmers Group